Selection of deep, energetically weak waves in seismic DSS records - D.M. Gryn’ (Геофизический журнал, 2020)
To solve direct problems of seismic, namely, to construct velocity DSS models we need to have a maximal number of hodographs of reflected waves from geological borders. The strongest reflections occur at a short distance from the explosion point. The more is the distance, the smaller the amplitude of vibrations of seismic reflected waves and more difficult their selection from the wave field. The object of the paper is a proposal of the ways for increasing information value of DSS data by selection of small amplitude reflected waves and their hodographs from the borders which occur at deep depths. The basis of the method is a difference method of spatial selection of hodographs of the target waves by the calculated or arbitrarily chosen direction. As a result the initial wave field is subdivided into the field with noise-waves of different origin and the wave field of efficient signals.